2022
DOI: 10.21037/jtd-21-1774
|View full text |Cite
|
Sign up to set email alerts
|

Is faster better? Impact of operative time on postoperative outcomes after VATS anatomical pulmonary resection

Abstract: Background: Video-assisted thoracic surgery (VATS) is now the preferred approach for standard anatomical pulmonary resections. This study evaluates the impact of operative time (OT) on post-operative outcomes after VATS anatomical pulmonary resection for non-small cell lung cancer (NSCLC). Methods:We retrospectively reviewed all consecutive patients undergoing VATS lobectomy or segmentectomy for NSCLC between November 2010 and December 2019. Postoperative outcomes were compared between short (<150 minutes) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
4
2
1
Order By: Relevance
“…However, left pneumonectomy might also bring about postoperative complications. Table 5 suggests that pneumonectomy and longer surgical time (challenging surgery) are independent risk factors for postoperative complications, which is consistent with the results of previous studies 31,32 . Foster et al 31 believe that a surgical duration greater than 150 min significantly increases the complications of the surgery, similar to the threshold of 148.6 min used for surgical difficulty appraisal in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, left pneumonectomy might also bring about postoperative complications. Table 5 suggests that pneumonectomy and longer surgical time (challenging surgery) are independent risk factors for postoperative complications, which is consistent with the results of previous studies 31,32 . Foster et al 31 believe that a surgical duration greater than 150 min significantly increases the complications of the surgery, similar to the threshold of 148.6 min used for surgical difficulty appraisal in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Table 5 suggests that pneumonectomy and longer surgical time (challenging surgery) are independent risk factors for postoperative complications, which is consistent with the results of previous studies 31,32 . Foster et al 31 believe that a surgical duration greater than 150 min significantly increases the complications of the surgery, similar to the threshold of 148.6 min used for surgical difficulty appraisal in the present study. Jiang et al 32 reckon that, compared to sleeve resection, pneumonectomy has a higher 30‐ and 90‐day mortality rates, and the overall incidence of postoperative complications, inclusive of bronchopleural fistula and acute respiratory distress syndrome, is significantly increased.…”
Section: Discussionsupporting
confidence: 92%
“…However, left pneumonectomy might also bring about postoperative complications. Table 5 suggests that pneumonectomy and longer surgical time (challenging surgery) are independent risk factors for postoperative complications, which is consistent with the results of preceding studies [30,31]. Foster et al [30] believe that a surgical duration greater than 150 minutes signi cantly increases the complications of the surgery, similar to the threshold of 144.5 minutes used for surgical di culty appraisal in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Prolonged operative time in MIS pulmonary resections has been reported to be associated with increased postoperative complications. [16][17][18] In this series, the mean operative time was 132.6 (98 to 223) min, which is lower than the threshold proposed by the cited authors at which complications are more frequently observed. In addition, a 25% decrease (mean 99.4 min) was observed in the second half of cases.…”
Section: Discussioncontrasting
confidence: 60%